(8y-x)(6y-x)(6x+4y)+(8y+x)(6y+x)(-6x+4y)

(8y-x)(6y-x)(6x+4y)-(8y+x)(6y+x)(-6x+4y)​

MariKharlova MariKharlova    2   06.09.2019 16:05    0

Ответы
vikaiero13 vikaiero13  06.10.2020 21:26

1) (48y²-8xy-6xy+x²)(6x+4y)+(48y²+8xy+6xy+x²)(-6x+4y)=(48y²-14xy+x²)(6x+4y)+(48y²+14xy+x²)(-6x+4y)= 288xy²+192y³-84x²y-56xy²+6x³+4x²y-288xy²+192y³-84x²y+56xy²-6x³+4x²y= 384y³-160x²y

2) (48y²-8xy-6xy+x²)(6x+4y)-(48y²+8xy+6xy+x²)(-6x+4y)=(48y²-14xy+x²)(6x+4y)-(48y²+14xy+x²)(-6x+4y)=288xy²+192y³-84x²y-56xy²+6x³+4x²y+288xy²-192y³+84x²y-56xy²+6x³-4x²y= 464xy²+12x³

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра